METHODOLOGICAL ASPECTS OF DISTANCE LEARNING - Mokhnachov, S. I. (Medical Informatics and Engineering, 2012)
Technologies of transfer of the medical and educational data on distance with the help of various telecommunication technologies, questions of remote training of doctors and pharmacists are considered. The idea and advantages of creation of the centers of a telemedicine and remote training, their profitability are proved. The choice of telecommunication technology for the most qualitative transfer of the telemedical data and carrying out of remote education is determined.